Juridical Analysis of Compensation Settlement for Unlawful Acts in Land Dispute Lawsuits: Case Study of Decision Number 111/PDT.G/2022/PN JMB - Munthe, Eunike Chairani Sukma; Prasetyo, Muhammad Arif (IJBLE Scientific Publications Community Inc., 2025)
An unlawful act is an act that is contrary to the legal norms prevailing in society and can harm other parties. In the context of Indonesian law, this unlawful act is regulated in Article 1365 of the Civil Code (KUHPerdata), which states that